2015
DOI: 10.2533/chimia.2015.136
|View full text |Cite
|
Sign up to set email alerts
|

Evolving P450pyr Monooxygenase for Regio- and Stereoselective Hydroxylations

Abstract: P450pyr monooxygenase from Sphingomonas sp. HXN-200 catalysed the regio- and stereoselective hydroxylation at a non-activated carbon atom, a useful but challenging reaction in classic chemistry, with unique substrate specificity for a number of alicyclic compounds. New P450pyr mutants were developed by directed evolution with improved catalytic performance, thus significantly extending the application of the P450pyr monooxygenase family in biohydroxylation to prepare useful and valuable chiral alcohols. Direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In our previous study, we expressed several P450 monooxygenases in Escherichia coli BL21­(DE3) and investigated their catalytic activity and enantioselectivity in the benzylic hydroxylation of halohydrocarbons and aromatic hydrocarbons. , P450pyr monooxygenase is a unique hydroxylase that catalyzes the asymmetric hydroxylation of N-heterocycles at nonactivated C–H bonds as well as alkanes at terminal or subterminal C–H bonds. Meanwhile, we found that some E. coli BL21­(DE3) strains harboring P450pyr variants , exhibited good enantioselectivity in the benzylic hydroxylation of halohydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we expressed several P450 monooxygenases in Escherichia coli BL21­(DE3) and investigated their catalytic activity and enantioselectivity in the benzylic hydroxylation of halohydrocarbons and aromatic hydrocarbons. , P450pyr monooxygenase is a unique hydroxylase that catalyzes the asymmetric hydroxylation of N-heterocycles at nonactivated C–H bonds as well as alkanes at terminal or subterminal C–H bonds. Meanwhile, we found that some E. coli BL21­(DE3) strains harboring P450pyr variants , exhibited good enantioselectivity in the benzylic hydroxylation of halohydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the CYP153 class of enzymes have long been recognized for their ability to catalyze the selective terminal oxidation of alkanes and fatty acids. This selectivity and specificity have been expanded on in recent years [28][29][30][31][32][33]. Despite their impressive regioselectivity, their application in industrial processes have been hindered by various limitations, including among others, requirement for redox partner proteins, cofactor regeneration, stability, and low activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also demonstrated that Sphingomonas sp. HXN-200 bacteria contain hydrocarbon-degrading enzymes [17,18]. The results of these studies suggest that Sphingomonas sp.…”
Section: Introductionmentioning
confidence: 99%